2021
DOI: 10.1186/s12870-021-02908-8
|View full text |Cite
|
Sign up to set email alerts
|

Genomic imprinted genes in reciprocal hybrid endosperm of Brassica napus

Abstract: Background Genomic imprinting results in the expression of parent-of-origin-specific alleles in the offspring. Brassica napus is an oil crop with research values in polyploidization. Identification of imprinted genes in B. napus will enrich the knowledge of genomic imprinting in dicotyledon plants. Results In this study, we performed reciprocal crosses between B. napus L. cultivars Yangyou 6 (Y6) and Zhongshuang 11 (ZS11) to collect endosperm at 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 96 publications
(181 reference statements)
2
13
0
Order By: Relevance
“…At the same time, TEs are a source of sRNAs, including siRNAs, that could potentially silence TEs through a post-transcriptional gene silencing (PTGS) process as discussed in Matzke and Mosher (2014) and Gill et al (2021). Similarly to Rong et al (2021) most differentially methylated TEs were found in 5 kbp gene flanking regions, as expected since 78% of TEs are in such loci in the employed Express 617 reference (Lee et al, 2020). Our results also outline that most TEs, DMRs and DE-siRNAS converged in .…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…At the same time, TEs are a source of sRNAs, including siRNAs, that could potentially silence TEs through a post-transcriptional gene silencing (PTGS) process as discussed in Matzke and Mosher (2014) and Gill et al (2021). Similarly to Rong et al (2021) most differentially methylated TEs were found in 5 kbp gene flanking regions, as expected since 78% of TEs are in such loci in the employed Express 617 reference (Lee et al, 2020). Our results also outline that most TEs, DMRs and DE-siRNAS converged in .…”
Section: Discussionsupporting
confidence: 73%
“…At the same time, TEs are a source of sRNAs, including siRNAs, that could potentially silence TEs through a post-transcriptional gene silencing (PTGS) process as discussed in Matzke and Mosher (2014) and Gill et al (2021). Similarly to Rong et al (2021) most differentially methylated TEs were found in 5 kbp gene flanking regions, as expected since 78% of TEs are in such loci in the employed Express 617 reference (Lee et al, 2020). Our results also outline that most TEs, DMRs and DE-siRNAS converged in 14 5 kbp gene flanking regions rather than in 5 kbp DEG flanking regions (Tables S30); thus, highlighting a putative conservation of most genetic functions by reducing the number of DMRs, DE-siRNAs and differentially methylated TEs in the proximity of DEGs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are around one hundred imprinted genes in maize and Arabidopsis, found in roughly equal proportions from both maternal and paternal genomes (Schon and Nodine 2017 ; Wyder et al 2019 ). While some genes have been found to be imprinted across species and have strong effects on endosperm function when their imprinting is perturbed (Grossniklaus et al 1998 ; Ingouff et al 2005 ; Makarevich et al 2008 ), there has been a wide debate regarding the conservation of the imprinted status of genes (Chen et al 2018 ; Hatorangan et al 2016 ; Klosinska et al 2016 ; Lafon-Placette et al 2018 ; Liu et al 2021 ; Pignatta et al 2014 ; Rong et al 2021 ; Roth et al 2018 ; Tuteja et al 2019 ; Waters et al 2013 ; Yang et al 2018 , 2020 ; Yoshida et al 2018 ). Yet, a conservation of imprinting targets may exist for molecular complexes or pathways rather than individual genes.…”
Section: Imprinting In Land Plants: a Spotlight On Angiospermsmentioning
confidence: 99%
“…In the present year, a work on the genomic imprinted genes of dicot B. napus endosperm provided 297 imprinted genes, including 283 MEGs and 14 PEGs. More specifically, (i) 36 of 297 imprinted genes were continuously imprinted during endosperm development; (ii) only 26 imprinted genes were specifically expressed in endosperm, while other genes were also expressed in other tissues of B. napus, rather than specifically in endosperm; and (iii) a total of 109 imprinted genes were clustered on rapeseed chromosomes [73]. Recently, imprinting status in two closely related dicot species, Arabidopsis and Capsella rubella, was analyzed, revealing that less than one-third of orthologous genes are imprinted in both species, and that genomic imprinting is a highly dynamic process [74].…”
Section: Endosperm-embryo Relationships: Imprinted Gene Expressionmentioning
confidence: 99%